IMPLEMENTASI PEMIKIRAN DAKWAH MOHAMMAD NATSIR DI DEWAN DAKWAH ISLAMIYAH INDONESIA PROVINSI ACEH - Raihan Raihan (Islam Futura, 2015)
Mohammad Natsir was one of the da’wa figure where his thoughts covered various fields. He was the founder DDII (Dewan Da'wah Islamiyah Indonesia) who was assessed consistently carried out the Islamic da’wa until the end of his life. As the result of his struggle, related to the vision and mission of the center of DDII, DDII Aceh should not be much different from that set by the center. But in reality, when it is seen through the aspect of the activities being carried out have not been fully applied by Aceh DDII. The result of this study shows that the struggle of Mohammad Natsir as well as the extension of the center management is related to the vision and the mission developed by the Aceh Provincial DDII is not different from that being set by the center. Similarly, the majority of programs are set by Aceh DDII has much in common with the da’wa activities that had been carried out by Mohammad Natsir when leading DDII, namely to conducted promoting and routine qur’anic recitation, building mosques, hampering the effort to silt the creed as well as other programs aimed at improving the Islamic da’wa quality. However, the performance of Aceh DDII is still seemed less productive due to the involvement of management which some still focus on less da’wa activities. In addition, the Aceh DDII is lack of operational funds in carrying out various activities which bring about some programs have been delayed, or even failure in its implementation.